Light reflection spectra as a tool for direct and real-time determination of biomass and pigments in the microalgae Microchloropsis salina. (April 2021) - Vinh, Trinh Quang; Trung, Tran Nam; Balasus, Jens; Sharma, Sulabha; Hegemann, Tim; Greulich, Simon; Khanh, Tran Quoc; Kaldenhoff, Ralf
To meet the increasing demand for mass-produced microalgae, production processes must be optimised and monitored. The herein described optical sensors provide an instantaneous and direct opportunity to monitor biological and biochemical information for microalgae cultivation. Combination of expertise in natural science and engineering, as well as the application of novel data acquisition and analysis methods, are required to develop an appropriate system for industrial purpose. Prior to this, the correlation between biological and physical parameters must be determined. In this work, we combined colour science with the experimentally determined dataset from the cultivation of Microchloropsis salina . Our results indicate a resilient correlation between algal biomass and its specific pigment concentration with the determined reflection spectrum. Data evaluation allowed us to establish identification models for contactless quantification of the respective biological parameter in large-scale automated bioreactors.